PO56 | Safety of anticoagulant treatment in patients with splanchnic vein thrombosis and history of portal hypertension-related bleeding (Bleeding, Thrombosis and Vascular Biology)
Background and Aims: Splanchnic vein thrombosis (SVT) can be associated to liver cirrhosis, or prothrombotic conditions, including myeloproliferative disorders, intra-abdominal inflammation, solid cancers, or surgery. While anticoagulation therapy improves outcomes in non-cirrhotic patients and reduces all-cause mortality in cirrhotic populations, its safety in patients with a history of portal hypertension (PH)-related bleeding is less clear. This systematic review examines the impact of anticoagulant therapy on re-bleeding risk in SVT patients with a history of PH-related bleeding.